The Epidemic at Savannah - Waring, James J. (Savannah, Georgia: Morning News Steam Printing House, 1879)
This substantial document deals with the yellow fever epidemic in Savannah in 1876. The author, James J. Waring, was the Chairman of the Dry Culture Committee (try imagining what that means without this book as a guide.) This book was a supplement to the Mayor's Report of January, 1879. The Mayor of Savannah is listed as J. F. Wheaton. The book includes a small, foldout, color map of Savannah as well as comprehensive information on this epidemic and what the city did to combat it. Illustrations include, besides drawings of bacteria, a Night Soil Van and a two-door (and presumably, two-seat) wooden privy. This plate was used earlier in the 1877 report entitled Evil and Remedy of the Privy System (no kidding). This book is very scarce. There is a copy listed in DeRenne (II 784) with full collation. No copies in NUC. Even without the front wrap, this is a desirable piece of Savannah history.
70FB45F7-C060-48E9-893C-70C0EFA27ED8 Waring, James J. The Epidemic at Savannah. Savannah, Georgia: Morning News Steam Printing House, 1879. The Epidemic at Savannah 1876 James J. Waring
Keywords: Rare Books; Georgia History; Savannah, Georgia; Epidemics